Reflective Teaching: An Approach to Enrich the English Teaching Professional Practice - Marian Lissett Olaya Mesa (Asociación Colombiana de Profesores de Ingles, 2018)
This study provides an overview and exploration of 23 national and international reflective teaching research reports. The purpose of this study is to determine the extent that reflective teaching can become a strategy for language teaching professional development. Based on content analysis four main topics emerged: (a) reflective teaching as an approach to enhance the language profession; (b) impact on teacher's performance; (c) support, time, and effort; and (d) in-service professional development. Conclusions indicated that reflective teaching is an alternative to raise awareness about English language teaching, and as a means to encourage teachers to open their minds, update their teaching methodologies, and make adjustments to their lessons.